The Non‑Penalization Machine: Mixed Movements in a Security‑driven European Border Order - Elessawy, Raghda (AUC Knowledge Fountain, 2026)
This thesis investigates how the non‑penalization principle for irregular border crossing is formally upheld yet effectively undermined in contemporary migration governance. It argues that non‑penalization now operates as a narrow, conditional and status‑dependent “machine” whose protections are fragmented across refugee, smuggling and trafficking regimes and heavily mediated by open‑textured conditions and domestic discretion. Part I reconstructs this doctrinal architecture, showing how key norms convert a humanitarian intuition into limited exceptions within a legal order that otherwise normalizes the criminalization of irregular movement. Part II situates this fragile framework within security‑driven and externalized forms of European border control, where punishment is displaced “at a distance” through offshore, outsourced and seemingly administrative practices. Tested against the reality of mixed movements, the analysis shows how status‑dependence, late recognition and security governance combine to produce a tiered structure of protection in which some people are shielded from sanctions while many others remain systematically punishable.